(untitled) (Research, Society and Development, 2025)
Introduction: Acute Kidney Injury (AKI) is an important health problem that can be predisposed by several conditions, including age, sepsis and comorbidities. Objectives: Evaluate the intensity of AKI in non-critical elderly patients admitted to an infirmary and its association with general mortality. Methods: Case-control, observational, retrospective and randomized study, matched by sex and age group, of elderly patients admitted to an infirmary over a period of one year. Non-critical patients aged over 65 years at the time of hospital admission were included and those with less than two serum creatinine measurements, undergoing renal replacement treatment before admission or coming from an intensive care unit were excluded. Results: 214 patients were evaluated, 50% of each sex, aged 77±7 (66–98) years old, with a hospital stay of 12±10 (1–85) days, of which 35 of the sample were .5% (n= 76) with AKI. There were 12.6% (n= 27) deaths and 1.4% (n= 3) required renal replacement treatment. There was an increase in the length of hospital stay in patients with AKI (p = 0.004) and was associated with mortality in those who developed AKI: stage 1 AKI: 21.3% (n = 13/62); AKI stage 2 - 25% (n = 1/4) and AKI stage 3 - 37.5% (n = 3/8). Conclusion: Elderly hospitalized patients frequently presented AKI, with progressive mortality with AKI staging, showing how important the early diagnosis is for clinical reversal.